Efektivitas Intervensi Cognitive Behavior Therapy dalam Menurunkan Ketakutan Kambuh pada Pasien Kanker - Rudi Rudi; Yati Afiyanti; Allenidekania Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the effectiveness of Cognitive Behavior Therapy (CBT) intervention in overcoming the fear of relapse in cancer patients. The research method used is a systematic review using five databases, namely Scopus, CINAHL, Embase, PubMed and Google search. The results showed that the provision of CBT intervention proved effective in reducing the fear of relapse in cancer patients. In conclusion, CBT intervention can be an alternative to overcome the fear of relapse in cancer patients. Keywords: Cognitive Behavioral Therapy, Fear of Relapse, Cancer Patients